Multiscale Modeling of Agglomerated Ceria Nanoparticles: Interface Stability and Oxygen Vacancy Formation - Kim, Byung-Hyun; Kullgren, Jolla; Wolf, Matthew J.; Hermansson, Kersti; Broqvist, Peter (Frontiers in Chemistry, 2019)
The interface formation and its effect on redox processes in agglomerated ceria nanoparticles (NPs) have been investigated using a multiscale simulation approach with standard density functional theory (DFT), self-consistent-charge density functional tight binding (SCC-DFTB) and a DFT-parameterized reactive force-field (ReaxFF). In particular, we have modelled Ce40O80 NP pairs, using SCC-DFTB and DFT, and longer chains and networks formed by Ce40O80 or Ce132O264 NPs, using ReaxFF molecular dynamics simulations. We find that the most stable {111}/{111} interface structure is coherent whereas the stable {100}/{100} structures can be either coherent or incoherent. The formation of {111}/{111} interfaces is found to have only a very small effect on the oxygen vacancy formation energy, Evac. The opposite holds true for {100}/{100} interfaces, which exhibit significantly lower Evac values, despite the fact that the interface formation eliminates reactive {100} facets. Our results pave the way for an increased understanding of ceria NP agglomeration.